2021
DOI: 10.5194/acp-21-10745-2021
|View full text |Cite
|
Sign up to set email alerts
|

Intensified modulation of winter aerosol pollution in China by El Niño with short duration

Abstract: Abstract. El Niño–Southern Oscillation (ENSO), a phenomenon of periodic changes in sea surface temperature in the equatorial central-eastern Pacific Ocean, is the strongest signal of interannual variability in the climate system with a quasi-period of 2–7 years. El Niño events have been shown to have important influences on meteorological conditions in China. In this study, the impacts of El Niño with different durations on aerosol concentrations and haze days during December–January–February (DJF) in China ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Some uncertainties in this study should be noted. Because the simulated aerosol concentrations in China are underestimated in the model in part due to the lack of treatment of nitrate and ammonium aerosols, strong wet scavenging, and less transformation from gas to particles 39 , the impact of aerosol emissions reductions on extreme precipitation could have been underestimated. In addition to the aerosol impacts on meteorological fields, studies also found that unfavorable atmospheric conditions could intensify aerosol pollution during the COVID-19 pandemic over the North China Plain 40,41 , which possibly explains the observed PM 2.5 increases in northern China (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Some uncertainties in this study should be noted. Because the simulated aerosol concentrations in China are underestimated in the model in part due to the lack of treatment of nitrate and ammonium aerosols, strong wet scavenging, and less transformation from gas to particles 39 , the impact of aerosol emissions reductions on extreme precipitation could have been underestimated. In addition to the aerosol impacts on meteorological fields, studies also found that unfavorable atmospheric conditions could intensify aerosol pollution during the COVID-19 pandemic over the North China Plain 40,41 , which possibly explains the observed PM 2.5 increases in northern China (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The pure ENSO influences can be more cleanly isolated using general circulation models driven by prescribed SSTs with and without ENSO signal (Zeng et al 2021). The composite differences in meteorological parameters between El Niño and La Niña years from MERRA-2 reanalysis are validated here by comparing with ERA5 reanalysis (figure S7).…”
Section: Conclusion and Discussionmentioning
confidence: 96%
“…AClean: same as Base, but anthropogenic emissions of aerosols and precursors over China are fixed at year 2017. concentration decreases with maximum decreases in the range of 12-18 μg m -3 . The low biases in CAM6 are caused by many factors including the lack of nitrate and ammonium representation, the absence of natural aerosols in the calculation of modeled PM2.5 concentrations, strong aerosol wet removal, and uncertainties in new particle formation, which have been reported in many previous studies (Yang et al, 2017a, b;Zeng et al, 2021;Ren et al, 2021). The model generally captures the percentage decreases in PM2.5 concentrations by about 20-40% in seven sub-regions over central-eastern China (Fig.…”
Section: Methodsmentioning
confidence: 88%
“…To mitigate the serious air pollution, China issued the Air Pollution Prevention and Control Action Plan in 2013 (Clean Air Alliance of China , 2013), in which a decrease in PM2.5 (PM with diameter less than 2.5 μm) by 15%-25% by year 2017, compared to 2013, was proposed for various regions of China. The emissions of major air pollutants have been reduced since then and aerosol concentrations have substantially decreased across China (Li et al, 2021). In 74 key cities in China, the annual average of observed PM2.5 concentrations decreased by 33.3% from 2013 to 2017 (Huang et al, 2018).…”
mentioning
confidence: 99%